Pengaruh Kepuasan Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan PT Kereta Api Indonesia (PERSERO): The Effect of Job Satisfaction and Work Motivation on Employee Performance at PT Kereta Api Indonesia (PERSERO) - Muhammad Rizki Januar; Murniyati Murniyati (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
Employee performance is a key factor in determining the effectiveness and success of an organization. This study aims to analyze the influence of job satisfaction and work motivation on employee performance, both partially and simultaneously. A quantitative approach was employed, with data collected through closed-ended questionnaires using a Likert scale distributed to employees. The sampling technique used was purposive sampling. The collected data were analyzed using SPSS statistical software. The results showed that job satisfaction had a significant effect on performance with a significance value of 0.007, but with a negative regression coefficient of -0.532. In contrast, work motivation had a significant positive effect on performance with a regression coefficient of 0.765 and a significance value of 0.009. Simultaneously, both variables had a significant effect on employee performance with an F-value of 4.619 and a significance level of 0.000, and an Adjusted R² value of 0.129. These findings highlight the importance of managing work motivation to improve employee performance.